WORK ENGAGEMENT, BURNOUT, AND QUALITY OF MIDWIFERY CARE: THE MEDIATING ROLE OF MIDWIFE PERFORMANCE IN A CROSS-SECTIONAL STUDY - Devy Lestari Nurul Aulia; Arum Dwi Anjani; Dainty Maternity; Sunesni (Pena Cendekia Insani, 2026)
This study examined the associations of work engagement and burnout with midwifery care quality through the mediating role of midwife performance in Batam City primary health centers. A cross-sectional study involving 156 midwives from all community health centers (Puskesmas), selected through purposive sampling, was conducted. Work engagement was measured using the Utrecht Work Engagement Scale, and burnout using the Maslach Burnout Inventory, while performance and care quality were assessed via instruments based on Indonesia’s Midwifery Service Standards. Data were analyzed using SEM-PLS with SmartPLS 4.0, including bootstrapping with 5,000 subsamples. Work engagement was positively associated with midwife performance (? = 0.481,p < 0.001) and care quality (= 0.356,p < 0.001), whereas burnout was negatively associated with both. Midwife performance significantly mediated these relationships, and the model explained 67.5% of the variance in care quality. Midwives’ psychological well-being is significantly associated with care quality, with performance serving as a critical mediating mechanism.